2012
DOI: 10.1093/jnci/djs187
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gut-Targeted 15-LOX-1 Transgene Expression on Colonic Tumorigenesis in Mice

Abstract: Expression of 15-lipoxygenase-1 (15-LOX-1) is decreased in many human cancers; however, the mechanistic significance of its decreased expression has been difficult to determine because its mouse homolog 12/15-LOX has opposing functions. We generated a mouse model in which expression of a human 15-LOX-1 transgene was targeted to the intestinal epithelium via the villin promoter. Targeted expression was confirmed by real-time reverse transcription-polymerase chain reaction and immunoblotting. When the 15-LOX-1 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 34 publications
2
51
0
Order By: Relevance
“…Downregulation of ALOX15 expression in human colorectal cancer cells is associated with upregulation of IL-1β, and re-expression of ALOX15 in colon cancer cells suppresses IL-1β expression [31]. Furthermore, transgenic expression of human ALOX15 in mouse colonic epithelial cells inhibits TNF-α and nuclear factor kappa B (NF-κB) signaling [32]. …”
Section: Alox15 Regulates Inflammation Through Multiple Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Downregulation of ALOX15 expression in human colorectal cancer cells is associated with upregulation of IL-1β, and re-expression of ALOX15 in colon cancer cells suppresses IL-1β expression [31]. Furthermore, transgenic expression of human ALOX15 in mouse colonic epithelial cells inhibits TNF-α and nuclear factor kappa B (NF-κB) signaling [32]. …”
Section: Alox15 Regulates Inflammation Through Multiple Pathwaysmentioning
confidence: 99%
“…Loss of ALOX15 expression is transcriptionally mediated [81] and independent of substrate availability [31]. While some earlier studies suggested that ALOX15 might have a procarcinogenic role, several lines of evidence, including more recent evidence [32, 82] have demonstrated that ALOX15 has a tumor-suppressing role, especially in colorectal tumorigenesis [74, 83]. ALOX15 re-expression in human colorectal cancer cells via pharmaceutical agents [21, 84, 85] or plasmid or adenoviral vectors [20, 70, 73] inhibits the growth of those cells in vitro and in vivo [86].…”
Section: Alox15 Inhibits Colorectal Tumorigenesismentioning
confidence: 99%
See 1 more Smart Citation
“…15-LOX-1 transgene expression was always decreased in the tumors that did develop. In the presence of expression of the 15-LOX-1 transgene, expression of TNF-a and its target-inducible nitric oxide synthase was decreased and activation of NFjB in colonic epithelial cells was inhibited [41]. These results indicate that 15-LOX-1 can serve as a tumor suppressor gene.…”
Section: -Lox-1 and Colorectal Cancermentioning
confidence: 87%
“…The nuclear factor-kappa B (NF-jB) pathway is involved in the mechanistic route to IBDs such as ulcerative colitis, Crohn disease, and CAC. However, expression of 15-LOX-1 is associated with reduced expression of NF-jB, tumor necrosis factor-alpha (TNF-a), and its target, inducible nitric oxide synthase (iNOS), all of which play well-known roles in the induction of colitis [41].…”
Section: -Lox-1 and Inflammatory Factorsmentioning
confidence: 99%